2013
DOI: 10.1371/journal.pcbi.1003233
|View full text |Cite
|
Sign up to set email alerts
|

Human Genome Replication Proceeds through Four Chromatin States

Abstract: Advances in genomic studies have led to significant progress in understanding the epigenetically controlled interplay between chromatin structure and nuclear functions. Epigenetic modifications were shown to play a key role in transcription regulation and genome activity during development and differentiation or in response to the environment. Paradoxically, the molecular mechanisms that regulate the initiation and the maintenance of the spatio-temporal replication program in higher eukaryotes, and in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
82
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 132 publications
19
82
1
Order By: Relevance
“…For example, the repressive mark H3K27me3 has been reported to associate with early to mid replication and with early and mid origins (Chandra et al, 2012;Julienne et al, 2013;Picard et al, 2014), as well as with late replication (Thurman et al, 2007). In our data, peaks of H3K27me3 appear to follow two different patterns.…”
Section: Replication Timing In Relation To Chromatin Packagingmentioning
confidence: 43%
See 2 more Smart Citations
“…For example, the repressive mark H3K27me3 has been reported to associate with early to mid replication and with early and mid origins (Chandra et al, 2012;Julienne et al, 2013;Picard et al, 2014), as well as with late replication (Thurman et al, 2007). In our data, peaks of H3K27me3 appear to follow two different patterns.…”
Section: Replication Timing In Relation To Chromatin Packagingmentioning
confidence: 43%
“…We found a similar association of early replication and active modifications in maize. Many active modifications (e.g., H3K4me2/3, H3K36me3, and H3ac) are typically found in the same regions of the genome (Roudier et al, 2011;Julienne et al, 2013) and are usually more indicative of gene expression than replication time . By selecting H3K4me3 and H3K56ac, we have likely captured a reasonable consensus of the open regions containing active histone marks within the cell types in the maize root tip.…”
Section: Replication Timing In Relation To Chromatin Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…When further investigating the spatial distribution of the P1, P2, P3 and P4 promoters along human chromosomes, our study reveals a remarkable gene organization in relation with the MRT. In 50% of the human genome that are covered by megabase-sized replication U-domains Julienne et al 2013), a significant enrichment of highly expressed P1 genes is observed in a closed neighbourhood of the early C1 initiation zones that border these domains. P2 promoters are mainly found in the mid-S C2 environment at finite distance (∼200-300 kb) from U-domain borders.…”
Section: Conclusion/perspectivesmentioning
confidence: 99%
“…In the third section, we perform a combinatorial analysis of chromatin marks in K562 and we describe the epigenetic content of the four prevalent chromatin states at gene promoters. In the fourth section, we study the coherence between promoter activity, as characterized by their 'small-scale' chromatin state, and the 'large-scale' chromatin environment (namely the C1, C2, C3 and C4 chromatin states found in Julienne et al (2013)). In this comparative analysis we emphasize the expected as well as the unexpected importance of gene density on the observed relationship between these two scales characterizing transcription and replication data respectively.…”
Section: Introductionmentioning
confidence: 99%